New Empirical Evidence on the Determinants of Capital Intensity: An Adaptive Comparison of Iran and China - Shojaie, Tooba; Tehranchian, Amir Mansour (International Journal of Economics and Financial Issues, 2018)
This research as an empirical study compares the effective factors with capital intensity in Iran and China. For this purpose, we use Auto Regressive Distributed Lag model during 1981-2012. The results show that for Iran’s economy in the short run, trade openness degree is the most effective factor in capital intensity. In the long run, the relative cost of production factors to capital-labor ratio, has the largest effect. The results also show that, for China’s economy, participation rate of production factors has the largest effect on capital intensity. Iran’s economy is labor intensive. Finally, the results show that Iran’s economy has more saving in capital factor but China’s economy has more saving in labor factor. Since Iran has advantages in producing labor-intensive goods, so the more increase in trade openness degree happens, the more labor would be employed. Then, investment in labor intensive goods would increase and it causes an increase in employment and growth.China can use its capacities and more capital in production in order to move toward economic prosperity. China needs to expand free trade based on comparative advantages. Keywords: Capital intensity, Heckscher-Ohlin theory, Labor force, Capital. JEL Classifications: C22, F14, O11